JAK1 inhibitor abrocitinib for the treatment of steroid-induced rosacea: case series - Xu, Bingyang; Xu, Zining; Ye, Shuhong; Sun, Hong; Zhao, Bin; Wu, Na; Wu, Jiawen (Frontiers in Medicine, 2023)
Abstract: Background. Steroid-induced rosacea is a severe withdrawal reaction which can occur after the frequent and excessive topical use of steroids on the face. The Janus kinase (JAK)-signal transducers and activators of transcription signaling pathway is involved in many biological processes and may play a role in the development of steroid-induced rosacea. Objective. To observe the efficacy and safety of the JAK1 inhibitor abrocitinib in the treatment of steroid-induced rosacea. Methods. Four Chinese female patients were treated with orally-administered abrocitinib, a selective JAK1 inhibitor with a good safety profile, for steroid-induced rosacea. Results. Abrocitinib treatment resulted in improved skin condition and lowered Dermatology Life Quality Index scores in each of the four patients. No discomfort was reported and no adverse effects were observed. Conclusion. The JAK1 inhibitor abrocitinib is a promising potential treatment for steroid-induced rosacea.